Optical inhibition of larval zebrafish behaviour with anion channelrhodopsins - Claridge-Chang, Adam (2017)
Optical silencing of activity provides a way to test the necessity of neurons in behaviour. Two light-gated anion channels, GtACR1 and GtACR2, have recently been shown to potently inhibit activity in cultured mammalian neurons and in Drosophila. Here, we test the usefulness of these channels in larval zebrafish, using spontaneous coiling behaviour as the assay.